2021
DOI: 10.2147/ccide.s297467
|View full text |Cite
|
Sign up to set email alerts
|

Should Quality of Glycemic Control Guide Dental Implant Therapy in Patients with Diabetes? Focus on: Peri-Implant Diseases

Abstract: Background and Aim: Traditionally patients with metabolic conditions such as diabetes mellitus are considered not suitable candidates for dental implant therapy due to increased risk of infection, impaired bone healing or the potential for vascular complications. Periimplantitis as the more progressive form of peri-implant disease involves bone loss and estimated to occur in nearly half of all implant cases long-term. Despite extensive research on association of hyperglycemia with dental implants in preclinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…This may be accounted for by the peri-implant crevicular fluid of patients with peri-implantitis exhibiting increased inflammation with higher levels of interleukin (IL) 1, IL-8, and tumor necrosis factor (TNF) α, as well as matrix metalloproteinase collagenase 8 relative to the crevicular fluid of healthy patients. 88,89 Increased expression of IL-8 and TNF-α has also been observed in the peri-implant crevicular fluid of individuals with poor glycemic control compared with wellcontrolled glucose levels and healthy individuals. 55,88 Current methods applied for the treatment of periimplantitis have focused on implant surface decontamination (with approximately 0.23 mm reduction in the probing depth after treatment 71 ), local and systemic administration of antibiotics (∼0.27−0.30 mm reduction in the probing depth 70,71 ), as well as regenerative procedures using different types of bone grafts and membranes (∼0.51 mm reduction in the probing depth).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may be accounted for by the peri-implant crevicular fluid of patients with peri-implantitis exhibiting increased inflammation with higher levels of interleukin (IL) 1, IL-8, and tumor necrosis factor (TNF) α, as well as matrix metalloproteinase collagenase 8 relative to the crevicular fluid of healthy patients. 88,89 Increased expression of IL-8 and TNF-α has also been observed in the peri-implant crevicular fluid of individuals with poor glycemic control compared with wellcontrolled glucose levels and healthy individuals. 55,88 Current methods applied for the treatment of periimplantitis have focused on implant surface decontamination (with approximately 0.23 mm reduction in the probing depth after treatment 71 ), local and systemic administration of antibiotics (∼0.27−0.30 mm reduction in the probing depth 70,71 ), as well as regenerative procedures using different types of bone grafts and membranes (∼0.51 mm reduction in the probing depth).…”
Section: Discussionmentioning
confidence: 99%
“…88,89 Increased expression of IL-8 and TNF-α has also been observed in the peri-implant crevicular fluid of individuals with poor glycemic control compared with wellcontrolled glucose levels and healthy individuals. 55,88 Current methods applied for the treatment of periimplantitis have focused on implant surface decontamination (with approximately 0.23 mm reduction in the probing depth after treatment 71 ), local and systemic administration of antibiotics (∼0.27−0.30 mm reduction in the probing depth 70,71 ), as well as regenerative procedures using different types of bone grafts and membranes (∼0.51 mm reduction in the probing depth). 48,49,71 The results obtained have indicated minimal bone attachment gain and probing depth reduction, 45,48 especially in individuals with pro-inflammatory Figure 7.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The evidence as to whether diabetes is a risk factor for PI was considered “inconclusive” in the 2017 World Workshop on the Classification of Periodontal and Peri-Implant Diseases and Conditions [ 18 ]. Nevertheless, studies reporting results regardless of the level of glycemic control should be carefully interpreted [ 83 ]. Poor glycemic status (PGS) may negatively modulate bone factors (OPG, transforming growth factor beta (TGF-β), osteopontin, osteocalcin) during healing and seems to be an important factor affecting implant complication rates, including MBL [ 84 ].…”
Section: Reviewmentioning
confidence: 99%
“…Multiple studies had evaluated the success and failure rates of dental implants in diabetic patients, and the results were conflicting; therefore, further investigations are needed [11][12][13]. Several studies have demonstrated that low-level laser treatment (LLLT) could enhance the initial stability of osseointegrated implants in animal models [14][15][16].…”
Section: Introductionmentioning
confidence: 99%